Translation to Brazilian Portuguese and Cultural Adaptation of the Craniocervical Dysfunction Index - Dias, Ana Carolina Marcotti; Doi, Marcelo Yugi; Mesas, Arthur Eumann; Fillis, Michelle Moreira Abujamra; Branco-Barreiro, Fatima Cristina Alves; Marchiori, Luciana Lozza de Moraes (International Archives of Otorhinolaryngology, 2018)
Introduction Functional disorders of the craniocervical region affect 77.78% of Brazilian teachers. Among the most common instruments used to assess craniocervical disorders in a detailed and objective way, none had been translated to Brazilian Portuguese and adapted to Brazilian culture.Objectives To translate to Brazilian Portuguese and to culturally adapt the Craniocervical Dysfunction Index (CDI).Method The first phase of the study consisted of the translation, synthesis, back-translation, and review of the contents by a committee of experts, who developed a trial version and sent all the steps to the original author. The trial version was applied to 50 teachers of an institution. The reliability and internal consistency were evaluated by Cronbach α. For the validation, the Brazilian Portuguese version of the CDI was correlated with the Visual Analogue Scale (VAS) domains for cervicalgia and evaluated by Spearman ρ.Result Some expressions were adapted to the Brazilian culture. Among the participants who did not report neck pain in the VAS, 84.21% suffered from craniocervical dysfunction acording to the CDI. Among the participants who reported neck pain in the VAS, 100% suffered from craniocervical dysfunction according to the CDI. The CDI showed good internal consistency and satisfactory reliability measured by Cronbrach α (α = 0.717). There was a strong correlation between the CDI and the VAS score (ρ = 0.735).Conclusion No difficulties were encountered in the translation and back-translation of the CDI, and no problems were observed regarding the trial version developed; therefore, the Brazilian Portuguese version of the CDI is a valid and reliable instrument to evaluate the functional alteration of the craniocervical region.
Keywords: neck pain; questionnaires; school teachers